Correction: Understanding and controlling the release mechanism of Escherichia coli in double W1/O/W2 emulsion globules in the presence of NaCl in the W2 phase. Issue 22 (11th February 2016) - El Kadri, Hani; Overton, Tim; Bakalis, Serafim; Gkatzionis, Konstantinos
Abstract : Correction for 'Understanding and controlling the release mechanism of Escherichia coli in double W1 /O/W2 emulsion globules in the presence of NaCl in the W2 phase' by Hani El Kadri et al., RSC Adv., 2015, 5, 105098–105110.